MICROPLÁSTICOS DE PET CONTENDO PREDNISONA ADSORVIDA COMO VETORES DE POLUIÇÃO - Latczuk, Izabelli Fiuza (2021)
Microplastics are micron-sized plastic particles often found in the environment, these materials can adsorb other contaminants on their surface and act as pollutant carriers. Drugs are also contaminants detected in the medium, therefore, this work sought to analyze the interaction between pet microplastics and prednisone through adsorption experiments. For this, a factorial planning of the rotational central composite design was used, varying pH, concentration of adsorbate and amount of adsorbent. With this study, it can be seen that the highest rate of adsorption, approximately 20.5 %, occurred for the test where pH = 4, concentration of prednisone = 8.38 mg L-1 and 500 mg of microplastics was used. Analyzing the kinetics, the model that best fits the experimental data is the pseudo-first order model and making use of isotherms, the one that best explains the system is the Freundlich isotherm, which assumes that adsorption can occur in multilayers and surface is heterogeneous. Analyzing the thermodynamic parameters, the system occurs spontaneously and endothermically. PET microplastics can adsorb prednisone in significant amounts and act as vectors of this pollutant, being increasingly harmful to the environment.